Universality and chaoticity in ultracold K+KRb chemical reactions - J. F. E. Croft (Nature Portfolio, 2017)
Studying chemical reactions near zero temperature in detail is challenging both in theory and practice. Here the authors report an explicit quantum mechanical study of the benchmark ultracold reaction between a K atom and a KRb molecule, important for future controlled chemistry experiments.